How do you solve #49- [ 3+ 10y - 4( y + 2) ] = - 5( 3y - 6) - [ 5( y - 1) - 9y + 21]#?

2 Answers
Jul 16, 2018

Answer:

Arrange the equation

Explanation:

#49 - 3 -10y + 4y + 8 = -15y + 30 -5y +5 +9y -21#

after getting rid of parantheses:

#49 - 3 +8 - 30 -5 +21 = -15y -5y +9y +10y -4y#

Now combine numbers on one side and y terms on the other:

#40 = -24y + 19 y#

#40 = -5y#

#y=-40/5 = -8#

Your answer is #y=-8#

Jul 16, 2018

Answer:

#y=-8#

Explanation:

Given: #49- [ 3+ 10y - 4( y + 2) ] = - 5( 3y - 6) - [ 5( y - 1) - 9y + 21]#
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
#color(blue)("Consider "-[3+10y-4(y+2)]#

Multiply inside the square brackets by #-1#

#-3-10y+4(y+2)#

#-3-10y+4y+8#

#-3+8 -10y+4y#

#color(white)("dd")+5 color(white)("dddd")-6y#

~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
#color(blue)("Consider " - 5( 3y - 6))#

Multiply everything inside the brackets by #-5#

#-15y+30#
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
#color(blue)("Consider "- [ 5( y - 1) - 9y + 21])#

Multiply inside the square brackets by #-1#

#-5(y-1)+9y-21#

#-5y+5+9y-21#

#+5-21-5y+9y#

#color(white)("d")-16color(white)("dddd")+4y#
~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~
#color(blue)("Putting it all back together")#

#49+5-6y=-15y+30-16+4y#

#54-6y=-11y+14#

#11y-6y=14-54#

#5y=-40#

#y=-8#